Pengembangan Elektronik Lembar Kerja Peserta Didik (E-LKPD) pada Materi Sistem Pencernaan Manusia Berbantuan Liveworksheet Kelas V SDN 19 Pangkalpinang - Sujia Aprisari; Romadon; Sisi Pitriyana (JBES (Journal Basic Education Skills), 2023)
This research was motivated by students lack of interest in the teaching materials used in learning. This caused by passive behaviours of students when looking for information related to learning materials that require real visualization such as material on the human digestive system. So, it was necessary to develop electronic student worksheets (E-LKPD) with the help of live worksheets that are valid and practical on the subject of the human digestive system in fifth grade. This study used Research and Development (R&D) using the ADDIE model which consisted of 5 stages, namely analysis, design, development, implementation, and evaluation. The subjects in this study were a class teacher and 30 students in VA class at SDN 19 Pangkalpinang. Techniques and data collection instruments used questionnaires and interviews. The data analysis technique was quantitative descriptive, which was assessed by 3 media experts and 3 material experts. Practicality data was obtained from the results of questionnaire analysis and interviews. Based on the results of the assessment the media validator obtained 90% (Very Valid) and the material validator obtained 95% (Very Valid). The results of the small group trial obtained 100% (Very Practical) and the large group trial obtained 100% (Very Practical). The fifth-grade class teacher's response questionnaire obtained 100% (Very Practical). Therefore, it can be concluded that the E-LKPD material on the human digestive system assisted by Liveworksheets for fifth grade of Elementary School is very valid and very practical to use.